Arthroscopic treatment of internal snapping hip - Magi, Gonzalo J. (Orthop J Sports Med, 2018)
INTRODUCTION: Internal snapping hip syndrome (ISHS) is caused by the iliopsoas tendon snapping over either the iliopectineal ridge or the anterior femoral head. Excellent results are achieved only with activity modification, rest, and stretching the iliopsoas muscle. The literature favors iliopsoas tendon release if conservative therapy fails. There is little evidence about the gold standard of this condition. OBJECTIVE: Describe clinical results, complicactions and recurrence rate of arthroscopic treatment of ISHS. METHODS: We included all patients who failed conservative treatment and were treated with arthroscopy for ISHS between March 2012 and March 2018. Patients with less than 2 years of follow up and previous surgery on the hip were excluded. We performed Ilizariturri´s technique with a transcapsular endoscopic release in central compartment. We registered modified Harris hip score (MHHS), Hip outcome score activity of daily living (EHOSDL), patients satisfaction, recurrence rate and complications. RESULTS: Eight patients were included. Average follow up was 36 months (range 24-60 months). MMHS improved from preoperative average score of 70 (range 62-72) to postoperative average of 93 (range 92 to 96). Average EHOSDL improvement was 30% (from 55% preoperative to 85% postoperative). All patients had excellent results. Average patient satisfaction was 8 (range 7-9). We had no recurrence or complications. CONCLUSION: Arthroscopic treatment of ISHS allowed us to obtain very good clinical results with no complications or recurrences with a minimum 2 years follow up.